Surgical Management of Extrahepatic Biliary Neuroendocrine Tumors: A Case Report - Ostadsharif, Negar; Firouzfar, Alireza; Nasri, Parto; Sanei, Behnam (Archives of Case Reports, 2025)
Extrahepatic biliary neuroendocrine tumors (EBNETs) are a rare group of neoplasms with varying characteristics, with 223 cases documented since their discovery. In this case report, an EBNET is described as a result of vague abdominal pain and significantly elevated liver function tests in a 41-year-old woman who presented with vague abdominal pain and elevated liver function tests. Despite the challenges faced in preoperative diagnosis, including the need to differentiate from cholangiocarcinoma, surgical intervention was successful. Due to the tumor’s complex nature, meticulous dissection and reconstruction were required, leading to crucial insights into surgical management. In addition to highlighting the rarity of EBNETs, this case emphasizes the importance of early detection and customized surgical approaches.